Modernidade, cultura popular e táticas de preservação na alvorada republicana - Sevcenko, Nicolau (Revista de História, 2003)
Based on Religiões do Rio, written by João do Rio, this article discusses how he managed to successfuly cross over the boundaries of his own culture, thus being able to witness the way by which the Black communities of Rio de Janeiro regained the spell once stolen by White conquerors, thereby challenging their domination.